Safety of unconventional antibody-drug conjugate L-DOS47 in a phase I/II monotherapy study targeting advanced NSCLC - Ramlau, Rodryg; Kowalski, Dariusz M.; Szczęsna, Aleksandra; Szczylik, Cezary; Ou, Young; Köbel, Martin; Siegers, Gabrielle M.; Gaspar, Kim J.; Lee, Brenda; Roszkowski-Sliz, Kazimierz (Frontiers in Oncology, 2025)
IntroductionTumor acidity is emerging as a hallmark of cancer and carcinoembryonic antigen-related cell adhesion molecule 6 (CEACAM6) expression is frequently increased in acidic tumors. L-DOS47, a novel antibody-drug conjugate (ADC), consists of jack bean urease cross-linked to anti-CEACAM6 nanobodies. L-DOS47 is thus both targeted to CEACAM6-expressing tumors and designed to improve tumor control by neutralizing the acidic tumor microenvironment (TME) through ammonia and bicarbonate production from local urea.MethodsThis open-label, non-randomized study evaluated safety and tolerability of L-DOS47 in Stage IIIB/IV non-small cell lung cancer (NSCLC) patients. The Phase I 3 + 3 dose escalation aimed to determine the maximum tolerated dose (MTD) of L-DOS47 administered once/week over 14 days followed by seven days rest. Phase II explored twice-weekly dosing.Results55/90 patients enrolled in Phase I received L-DOS47 up to 13.55 μg/kg. Although one dose-limiting toxicity (DLT) occurred in a patient at 5.76 μg/kg, MTD was not reached. Common treatment-emergent adverse events (TEAEs), reported by 38% of patients, were respiratory/thoracic/mediastinal disorders including dyspnea. No complete (CR) or partial responses (PR) were observed in Phase I or Phase II, despite the latter’s intensified dosing regimen; however, Phase I post-hoc exploratory analyses found that progression-free survival (PFS) was significantly extended at doses ≥5.76 μg/kg (P=0.0203). Anti-L-DOS47 antibody (ADA) titers were not associated with AE or shorter PFS. Immunohistochemistry (IHC) screening of an unrelated cohort revealed high CEACAM6 expression in 45.2% NSCLC cases.ConclusionsL-DOS47 monotherapy was well tolerated at doses up to 13.55 μg/kg. No CRs or PRs were observed but extended PFS was associated with higher doses. Screening for CEACAM6 expression may select patients who are more likely to derive benefit from L-DOS47.Clinical Trial Registrationhttps://www.clinicaltrialsregister.eu/ctr-search/search; EudraCT Identifier: 2010-020729-42 (May 6, 2010).